Penyakit Peptik dan Misoprostol - Raini, Mariana; Isnawati, Ani (Jurnal Kefarmasian Indonesia, 2009)
Peptic mucus synthesize especially prostaglandine E2 and 12. Prostaglandine E2 and l2 can impede acid secrete and stimulate mucus and bicarbonate secretion. Misoprostol, a synthetic methyl ester analogue of prostaglandin is both a powerful inhibitor of gastric secretion and is able to protect the gastroduodenal mucosa from damage. Misoprostol and other prostaglandine derivatives can be alternative drug of peptic ulcer relapse because the metyl ester of prostaglandin exert an antisecretion and protective effects on peptic mucus. The clinical eﬂectiveness of misoprostol is comparable to cimethidin in short term treatment of peptic and duodenum ulcer as well as reducing duodenal ulcer relapse. Misoprostol may prevent gastrointestinal and peptic ulcer in long term treatment of Non Steroid Anti Inflamation Drug. The side eﬂect of misoprostol is cervix maturation and uterotonic. This article describe misoprostol eﬂecliveness on peptic and duodenum ulcer treatment.